Role of Garlic in Chronic Diseases: Focusing on Gut Microbiota Modulation - Wei Quan Lim; Jia Ying Cheam; Jodi Woan-Fei Law; Vengadesh Letchumanan; Learn-Han Lee; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Garlic is a herb and has been used as a spice with a long history in different types of cuisine. Garlic and its components are believed to be able to bring benefits to the health of an individual. The gut microbiota is closely related to an individual's health, and garlic is shown to have an effect on the gut microbiota as well. Hence, this literature review aims to portray the uses of garlic and its bioactive constituents on human health, particularly looking at how it modulates the gut microbiota and subsequently affects an individual's health directly or indirectly. These studies have shown the ameliorative effects of garlic and its bioactive constituents on various chronic diseases, including hypertension, diabetes mellitus, hyperlipidaemia and liver diseases.